2017
DOI: 10.1681/asn.2016121308
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Correction of Olfactory Deficits in Kidney Disease

Abstract: Patients with CKD suffer from food aversion, anorexia, and malnutrition. Although olfaction has a significant role in determining food flavor, our understanding of olfactory impairment and of the olfaction-nutrition axis in patients with kidney disease is limited. We quantified odor identification, odor threshold, and subjective odor perception in a cohort (=161) comprising 36 participants with CKD, 100 participants with ESRD, and 25 controls. We investigated olfaction-nutrition associations in these participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…Poor nutritional status Sinonasal/rhino-cerebral mucormycosis mainly presents as headache, facial swelling and pain (especially over affected areas), nasal discharge, and necrotic lesions on the face, nasal cavities, or palates [4,45] Rhino-cerebral form is most common form of mucormycosis in RTRs [4] Maxillary and ethmoid sinuses are mainly affected [45] Olfactory loss/ dysfunction 56% of patients with ESKD are affected [48] Exact mechanism is unknown It might result from uremia-induced negative effect on peripheral nerve conduction and central cognitive functions [47] Might be reversible-improvement of proper olfaction observed after renal transplantation and after dialysis session [47] Olfactory identification and discrimination are mainly affected; thresholds seem to remain unchanged [47] CT of paranasal sinuses before organ transplant not recommended in asymptomatic individuals because of the high rate of false positive results [44] Relatively low incidence of rhinosinusitis in RTRs might result from persistent low-dose prednisone therapy withholding the inflammatory responses that frequently promote CRS [44] Voice dysfunction Hoarseness 24-60% of patients with ESKD are affected [50] Potential mechanism [15] Excessive fluid and toxins accumulation, and acidbase imbalance Vocal cord edema Decreased pulmonary function Abnormal coordination between central nervous system and peripheral phonatory structures Laryngeal muscles fatigue Patients with ESKD on HD might suffer from temporary post-dialysis hoarseness as a result of HD-induced dehydration, reduction of the vocal cord size and increase in subglottic pressure [50] Bony changes…”
Section: Uremia Hyperglycemiamentioning
confidence: 99%
See 2 more Smart Citations
“…Poor nutritional status Sinonasal/rhino-cerebral mucormycosis mainly presents as headache, facial swelling and pain (especially over affected areas), nasal discharge, and necrotic lesions on the face, nasal cavities, or palates [4,45] Rhino-cerebral form is most common form of mucormycosis in RTRs [4] Maxillary and ethmoid sinuses are mainly affected [45] Olfactory loss/ dysfunction 56% of patients with ESKD are affected [48] Exact mechanism is unknown It might result from uremia-induced negative effect on peripheral nerve conduction and central cognitive functions [47] Might be reversible-improvement of proper olfaction observed after renal transplantation and after dialysis session [47] Olfactory identification and discrimination are mainly affected; thresholds seem to remain unchanged [47] CT of paranasal sinuses before organ transplant not recommended in asymptomatic individuals because of the high rate of false positive results [44] Relatively low incidence of rhinosinusitis in RTRs might result from persistent low-dose prednisone therapy withholding the inflammatory responses that frequently promote CRS [44] Voice dysfunction Hoarseness 24-60% of patients with ESKD are affected [50] Potential mechanism [15] Excessive fluid and toxins accumulation, and acidbase imbalance Vocal cord edema Decreased pulmonary function Abnormal coordination between central nervous system and peripheral phonatory structures Laryngeal muscles fatigue Patients with ESKD on HD might suffer from temporary post-dialysis hoarseness as a result of HD-induced dehydration, reduction of the vocal cord size and increase in subglottic pressure [50] Bony changes…”
Section: Uremia Hyperglycemiamentioning
confidence: 99%
“…Studies showed that the sense of smell could be affected in patients with CKD. It was reported that patients with CKD, mainly those with ESDK on dialysis, had moderately but significantly decreased olfactory function [47,48]. The prevalence of olfactory loss reached 56% of patients with ESRD [48].…”
Section: Sinonasal Dysfunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of olfaction included 100 dialysis patients (94 on HD) and 25 controls. Dialysis patients had a lower mean odor identification score than controls (67% vs 84%) as well as a higher odor threshold . An association of olfactory deficits with nutritional parameters could not be clearly shown.…”
mentioning
confidence: 77%
“…Dialysis patients had a lower mean odor identification score than controls (67% vs 84%) as well as a higher odor threshold. 17 An association of olfactory deficits with nutritional parameters could not be clearly shown. Intranasal theophylline increased odor identification score in five of seven dialysis patients.…”
Section: Reanalysis Of Data On 3762 Hd Patients From a 3-year Prospecmentioning
confidence: 98%